Characterization of the low-noise drone propeller with serrated Gurney flap - Noda, Ryusuke; Ikeda, Teruaki; Nakata, Toshiyuki; Liu, Hao (Frontiers in Aerospace Engineering, 2022)
Drones, which have become increasingly popular in recent years, produce a lot of noise due to the movement of their propellers. When flying near humans, especially as in urban situations, noise suppression is critical. It has been demonstrated that noise can be minimized by increasing propeller lift per unit rotation speed and decreasing propeller rotation speed by expanding propeller area or designing the airfoil shape. This study developed a new structure, serrated Gurney flap, by merging the Gurney flap, which is the trailing-edge structure of an airfoil, and the serration, which is the low-noise structure found in an owl feather, and studied its performance through experiments and numerical simulations. The results indicated that the structure can boost the propeller’s lift coefficient while reducing the vortex separation induced by the Gurney flap and suppress propeller noise by slowing the propeller. Further modification of its structure may result in improved efficiency as well as decreased noise level.